International students' experiences of othering in tertiary education in South Africa: an exploratory study - Lobakeng, Tsholofelo (Rhodes University, Faculty of Humanities, Department of Psychology)
Despite rising cases of xenophobia in South Africa, international students remain committed to enrolling in its universities. Surprisingly, there is limited research looking into xenophobia in tertiary institutions. Therefore, the present study aimed to contribute to the scarcity of knowledge on the experiences of international students in South Africa. Thus, the study explored experiences of Othering among international students in tertiary education in South Africa and how they make sense of these experiences. Purposive and snowballing sampling techniques were employed to recruit international students (N=5) from Botswana, China, Zambia, and Zimbabwe. Data was collected through semi-structured, face-to-face online interviews. Participants reported experiencing a variety of non-violent forms of Othering, such as feeling excluded due to the intentional use of local languages in both classroom and social settings; being rejected by local students who refused to work with them; and being accused of stealing opportunities from local students. At an institutional level, participants reported systemic Othering rooted in unsupportive policies and practices that led to a negative and oppressive environment. The findings support previous research studies that purport the Othering of international students in higher education in South Africa mainly manifests through non-violent and covert forms. Moreover, participants attributed Othering of immigrants to racism, a perceived lack of exposure to diversity among locals, perceived lack of compassion for immigrants, and the tendency to scapegoat immigrants for the lack of employment opportunities in the country. The findings underscore the intricate nature of Othering and the need for further research to gain a greater understanding of this complex phenomenon. Furthermore, the findings highlight the importance of implementing effective strategies of inclusion and integration of international students at these institutions of higher learning.
Keywords: Other (Philosophy); Afrophobia; Students, Foreign -- South Africa; Prejudices; Xenophobia in education; Education, Higher Social aspects